Bullying, Depression and Anxiety among Secondary School Students of Illam, Nepal - Yakha, Bhim Maya; Lama, Sami; Sapkota, Nidesh; Pradhan, Nirmala (Journal of Karnali Academy of Health Sciences, 2021)
Background: Bullying is an intentional act of hurt and frighten others, it is common in schools. Different kind of bullying student may include physical, verbal, emotional and cyber bullying in the school. Objectives: To assess bullying, depression and anxiety among students and to find out association between bullying, depression and anxiety. Materials and method: A descriptive cross-sectional study design was adopted with sample size of 306. Simple random sampling technique was used to select the sample. Bullying (physical, verbal, emotional, sexual and cyber bullying) questionnaire was developed on the basis of Olweus Bullying Profile, Depression and anxiety was assessed using Beck Depression Inventory (BDI II) and Beck Anxiety Inventory (BAI). Data were analyzed using descriptive and inferential statistics with SPSS version 16. Results: Present study found that 112 (37%) of respondents had experienced bullying among them physical bullying 41(36.6%), verbal bullying 40 (35.7%), emotional bullying 10 (8.92%), sexual bullying 11(9.82%), and cyber bullying 10 (8.92%). More than half (52.6%) of the respondents had minimal depression followed by mild depression 35.6%. More than two-third (69.9%) of the respondents had low anxiety. Conclusion: Bullying is common in schools. Minimal Depression and low anxiety were common in students which ultimately leads to suicidal ideation. There was significant association between physical, verbal, and sexual bullying with gender and obtained percentage in last year summative annual exam. Awareness program should be initiated to identify bullying and proper reporting which will ultimately improve the mental health of school students.